Les partenaires éducatifs de la préscolarisation en Inde du Sud dans un espace de concurrence - Émilie Ponceaud-Goreau (Les éditions de la Maison des sciences de l'Homme, 2017)
In India, since the 1970s, centers called anganwadis have welcomed children under the age of six free of charge. This place promotes the preconditions for a better schooling. While the emergence of preschooling in India is a public initiative, private actors are now very important and families are looking for this kind of structures. By choosing to enrol their child privately before reaching the age of six (which marks the start of compulsory schooling), they express their desire to enter the formal education system. These changes are studied through the situation of a district of Muthialpet, in the territory of Pondicherry. The microgeographic frame of analysis highlights preschool actors' role as well as the recent actions of the State engaged in a process of repositioning and ex-post control.